Interfacial Engineering for Fabricating High‐Performance Field‐Effect Transistors Based on 2D Materials. Issue 6 (30th April 2018) - Gao, Feng; Yang, Huihui; Hu, PingAn
Abstract: Traditional scaled complementary metal–oxide–semiconductor field‐effects transistors (FETs) are currently approaching physical limitations and are confronted with bottlenecks in their development. The increasing demands of FETs with high electronic performance and integration density have strongly motivated the exploration of novel channel materials, among which 2D materials are emerging as ideal candidates. In particular, 2D materials possess unique immunity to the short channel effects and also facilitate the realization of flexible microelectronic devices. Interface engineering is pivotal for optimizing the performance of traditional electronics, as well as 2D layered semiconductor electronics. So far, enormous efforts have been made to develop high‐performance FETs based on 2D materials. Here, a summary of the recent progress in 2D FET devices is presented, with a focus on the technologies and methodologies of interface engineering in 2D semiconductor FETs. Corresponding strategies are presented, including tuning the Schottky barrier height, optimizing the interface morphology, and so on. In the last part, the possible developing trends for 2D FET devices in the future are discussed. Abstract : Field‐effect transistors (FETs) based on 2D materials possess excellent performance, which gives them great potential for logic circuits, flexible electronics, and sensors. Interface engineering plays a crucial role in fabricating high‐performance FETs. Strategies including employing suitable electrodes and dielectrics are reviewed.